Podoplanin, α-Smooth Muscle Actin or S100A4 Expressing Cancer-Associated Fibroblasts Are Associated with Different Prognosis in Colorectal Cancers - Choi, Song-Yi; Sung, Rohyun; Lee, Sang-Jeon; Lee, Taek-Gu; Kim, Nayoung; Yoon, Soon Man; Lee, Eun Jeoung; Chae, Hee Bok; Youn, Sei Jin; Park, Seon Mee (Journal of Korean medical science, 2013)
The interactions between the tumor microenvironment and tumor cells determine the behavior of the primary tumors. Whether cancer-associated fibroblasts (CAF) have a tumor progressive or a protective role likely depends on the type of tumor cells and the CAF subpopulation. In the present study, we analyzed the prognostic significance of CAF subpopulations in colorectal cancer (CRC). CAF phenotypes were analyzed in 302 CRC patients by using antibodies against podoplanin (PDPN), α-smooth muscle actin (α-SMA), and S100A4. The relationship between the CAF phenotypes and 11 clinicopathological parameters were evaluated and their prognostic significance was analyzed from the disease-free and overall survival times. We observed that at the tumor invasive front, PDPN CAFs were present in 40% of the cases, and S100A4 or α-SMA CAFs were detected in all the cases. PDPN/S100A4 and α-SMA/S100A4 dual-stained CAFs were observed in 10% and 40% of the cases, respectively. The PDPN(+) CAFs were associated with 6 favorable clinicopathological parameters and prolonged disease-free survival time. The PDPN(-)/α-SMA(high) CAFs were associated with 6 aggressive clinicopathological parameters and tended to exhibit shorter disease-free survival time. On the other hand, the PDPN(-)/S100A4(high) CAFs were associated with 2 tumor progression parameters, but not with disease prognosis. The PDPN(+) CAF phenotype is distinct from the α-SMA or S100A4 CAFs in that it is associated with less aggressive tumors and a favorable prognosis, whereas the PDPN(-)/α-SMA(high) or PDPN(-)/S100A4(high) CAFs are associated with tumor progression in CRC. These findings suggest that CAFs can be a useful prognostic biomarker or potential targets of anti-cancer therapy in CRC.